An Assessment of 2016 National Healthcare Safety Network (NHSN) and National Electronic Disease Surveillance System (NEDSS) Clostridium difficile Infections (CDI) in Nebraska. (4th October 2017) - Pedati, Caitlin; Sullivan, Madison; Drake, Margaret; Keyser, Alison; Safranek, Tom; Tierney, Maureen
Abstract: Background: In 2016 all acute care hospitals, inpatient rehab facilities, and PPS-exempt cancer facilities in Nebraska were required to report laboratory identified (LabID) Clostridium difficile infections (CDIs) to the National Healthcare Safety Network (NHSN). Test results indicating CDIs must be reported to the Nebraska Department of Health and Human Services (NDHHS) via the National Electronic Disease Surveillance System (NEDSS). NHSN and NEDSS represent unique sources of CDI reports in Nebraska. Methods: The NHSN Nebraska database was queried for CDIs reported in 2016. All lab tests indicating a CDI in 2016 were extracted from NEDSS. These extracts were analyzed to assess descriptive epidemiologic variables and compared for differences. Results: In 2016 there were 1, 546 CDI LabID events reported to NHSN Nebraska from 28 facilities. There were 249 outpatient CDIs and 1, 297 inpatient CDIs. Infections were further characterized as community-onset ( N = 773), community-onset, healthcare facility associated ( N = 206), and hospital onset ( N = 567). An average of 128 CDIs were reported per month (range: 111–155). In 2016 there were 2, 177 lab results indicating a CDI reported to NEDSS among Nebraska residents from 42 facilities. Patient ages ranged from 4 months to 104 years (mean = 58 years). An average of 181 CDIs were reported per month (range: 151–218). Comparison of the two data sources found 781 reports among 591 unique patients at 11 facilities that were made to NHSN and were not in NEDSS. Additionally, there were 1, 092 reports from 931 unique patients at 12 facilities that were made to NEDSS and should have been made to NHSN but were not. There were 9 shared facilities that accounted for the majority of these discrepancies. Conclusion: NHSN and NEDSS represent two unique data sources that allow for a more comprehensive assessment of CDIs. The number and type of facility that report to each system is slightly different but there is some overlap. Therefore, this comparison allows for detection of a greater number of reports overall and also provides an opportunity for data validation. This assessment identified discrepancies in reporting among 9 facilities that can be targeted for further collaborative efforts to improve CDI reporting and management in Nebraska. Disclosures: All authors: No reported disclosures.